The role of infrastructure development in economic growth in Malaysia / Nurul Atiqah Alias - Alias, Nurul Atiqah (Faculty of Business and Management, 2018)
The aim of study is to investigate the relationship between infrastructure indicators variables which is consist of energy consumption, electricity production, telecommunication density and water supply towards economic growth. The study used Multiple Linear Regression in order to find the relationship among dependent variable and independent variables. The data is collected from year 1980-2016 and conduct by yearly basis. From the result, it reveals that water supply have positive relationship towards economic growth. While, energy consumption, electricity production and telecommunication density have negative relationship towards economic growth. This result give additional understanding of the relationship between infrastructure variables and economic growth and should be useful for regulator, economist and investor.